Kazakh diaspora in people’s Republic of China and their social status - Askhat, G.; Zhabina, Z.R.; Khairullayeva, V.K. (Opción, 2019)
The article focuses on the Kazakh diaspora, mainly the article examines the formation of Kazakh Diasporas in the People’s Republic of China and their political, economic and social status via comparative qualitative research methods. In result, an objective study of the issues of diaspora development can play a positive role in solving the problems of further preserving and consolidating civil peace, strengthening friendship and interethnic harmony. In conclusion, the situation which is happening currently in China proves that Kazakhs are experiencing another tragic stage in its history